View of the Sitaleshwar Temple from the south - Temples of India Project Team (Jio Institute, 2024)
The plinth of the Sitaleshwar Temple has basal mouldings and jangha (wall) carved with bhadra (central offsets). The shikhara (superstructure) has collapsed, and presently, it has a flat roof with a small dome added later at the centre.